2020
DOI: 10.3390/ijerph17228506
|View full text |Cite
|
Sign up to set email alerts
|

Equity to Urban Parks for Elderly Residents: Perspectives of Balance between Supply and Demand

Abstract: As population ages, ensuring that the elderly get their due rights has become a common concern of scholars in many fields. However, as an important public service facility in daily life of elderly, the research on the equity of urban parks is mostly based on the evaluation of accessibility. The equity of the elderly's access to urban parks services has been rarely discussed from the perspective of supply and demand balance. In the context of the concept of spatial equity, we used urban parks in the main city o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Demographic factors, such as socioeconomic status [30] and race [31], are also included to explore the matching of supply and demand of public service facilities. For example, some studies examined the matching of supply and demand of different types of urban parks and considered the actual travel mode of the elderly [32]. In addition, some studies also put forward the matching index of supply and demand to explore the coupling relationship between the index and urban development factors.…”
Section: Introductionmentioning
confidence: 99%
“…Demographic factors, such as socioeconomic status [30] and race [31], are also included to explore the matching of supply and demand of public service facilities. For example, some studies examined the matching of supply and demand of different types of urban parks and considered the actual travel mode of the elderly [32]. In addition, some studies also put forward the matching index of supply and demand to explore the coupling relationship between the index and urban development factors.…”
Section: Introductionmentioning
confidence: 99%
“…Urban settings in different countries have significant inequalities in the distribution of physical infrastructure that affect residents' quality of life; for example, residents in historic quarters of Changting in China, Glasgow in the UK and Berlin in Germany suffer from lack of access to basic services such as transportation, health care, and green space [1,3,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…When looking at deprived urban areas within a city, it is easy to conclude that residents are at greater health risks from natural and manmade hazards, including natural disasters, pollution, noise, and traffic toxicity [20]. In these deprived areas, access to the natural ecosystem is limited, especially in terms of access to natural landscapes, and there is a disparity between high population density and the low coverage of green space [3,5,7,13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the United Nations survey report, it has been observed that the world population has risen annually and that the proportion of the global population over 60 is expected to exceed 23 percent by 2050. (Guo et al, 2020). Increasing recognition of the challenge of active aging is greatly affected by the role of the elderly in society, as demonstrated in the United Nations report.…”
Section: Introductionmentioning
confidence: 99%